(untitled) (Journal of the College of Basic Education, 2022)
Turn-taking in drama denotes the interplay between two or more contributors in which they come to the contentious operation process shared presumptions and prospects about what it is, how it improves, and the kind of taking part they anticipate to create. The players, who take the reins of the interlocution turn-taking operations, try to use different crucial tools to take notice of the recipients indicating their perception and affection illustrating certain cases. In 1974, Sacks, Schegloff and Jefferson planned a model for the systematization of turn-taking in English interlocution by native speakers. This model is called a simplest systematics for the arrangement of turn-taking for interlocution. This study counts on this model for the analysis of turn-taking in Hamlet..A number of extracts has been selected for the data analysis, with the aim of assigning turn-taking pragmatically. Making use of the syntactic and semantic behavior of these texts, types, functions, and realisations of turn-taking have been investigated. The researcher has arrived at the following conclusions: There is monologue vs. dialogue distinction in relation to turn-taking. Considering these two plays, it has been found that there is a difference between dialogue which is frequently characterized by turn-taking and monologue when one speaks longer than expected in a turn in as it is found in Hamlet .The society and culture play a big role, affecting turn-taking. The society which is the surrounding environment affects turn-taking system to a great extent. In both plays, the social rank plays is also important, there are mother-son talk, father (ghost)-son talk, friends talk, each has its own way of talk. The psychology of the participants affects turn-taking greatly. The psychology of the participant mostly affects turn-taking system too much. It may cause a rapid continuous speech on the one hand; it may also cut the speeches into pieces on the other hand. It may also cause overlaps, interruptions, or pauses. After conducting the analysis, the researcher has arrived at the following conclusions: The society which is the surrounding environment affects turn-taking system to a great extent. Friends talk is mostly intimate, it opens with greeting and navigates into the topic. The friend language depends on the situation. The Psychology of the participants affects Turn-taking greatly. The psychology of the participants mostly affects turn-taking system to a great extent. To achieve this end, it is hypothesized that there is a strong connection between turn-taking, society and psychology. The social rules are the ranks and the relationships between the participants. and the turns in Hamlet are mostly long. This length of turn-taking let the study of turn-taking be divided into two sections: dialogue and monologue.